CRISPR/Cas9-mediated genome editing of RsGL1a and RsGL1b in radish (Raphanus sativus L.) - Muto, Naoki; Matsumoto, Takashi (Frontiers in Plant Science, 2022)
The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) is a powerful tool widely used for genome editing in various organisms, including plants. It introduces and facilitates the study of rare genetic mutations in a short time and is a potent tool to assist in plant molecular breeding. Radish (Raphanus sativus L.) is an important Brassicaceae vegetable cultivated and consumed worldwide. However, the application of the CRISPR/Cas9 system is limited by the absence of an efficient transformation system in radish. This study aimed to establish CRISPR/Cas9 system in radish employing the Agrobacterium-mediated genetic transformation system reported recently. For this purpose, we performed genome editing using the CRISPR/Cas9 system targeting the GLABRA1 (GL1) orthologs, RsGL1a and RsGL1b, that induces leaf trichome formation in radish. A Cas9/single guide RNA (sgRNA) vector with a common sgRNA corresponding to RsGL1a and RsGL1b was transferred. A total of eight T0 plants were analyzed, of which six (editing efficiency 75%) had a mutated RsGL1a allele, five (62.5%) had a mutated RsGL1b allele, and five showed mutations in both RsGL1a and RsGL1b alleles. Most mutations in T0 plants were short (<3 bp) deletions or insertions, causing frameshift mutations that might produce non-functional proteins. Chimeric mutations were detected in several T0 generation plants. In the T1 generation, the hairless phenotype was observed only in plants with knockout mutations in both RsGL1a and RsGL1b alleles. The majority of mutant alleles in non-chimeric mutant plants detected in T0 plants were stably inherited in the T1 generation. In conclusion, we successfully knocked out RsGL1a and RsGL1b using the CRISPR/Cas9 system and demonstrated that both RsGL1a and RsGL1b independently contribute to the induction of leaf trichome formation in radish. The findings prove the feasibility of genome editing in radish using a CRISPR/Cas9 system that could accelerate its molecular breeding to improve agronomically desirable traits.